Dampak Program Corporate Social Responsibility terhadap Pendapatan Anggota Kelompok Pembudidaya Ikan Mina Kepis Desa Sumberadi Kecamatan Mlati Kabupaten Sleman - Anita Febrina; Suadi Suadi; Hery Saksono (Universitas Gadjah Mada, 2015)
The objective of this research is to determine the type, benefi ts, and impact of Corporate Social Responsibility (CSR) programs of Bank Indonesia on income of fi sh farmer group (KPI) Mina Kepis at Sumberadi village, Sleman Regency. The study was conducted from January to March 2015. All member of KPI were selected as respondents, with total number of 28 persons. The study showed that CSR program in the form of physical infrastructure assistance such as major production facilities (pool and hatchery) and supporting infrastructure (parking facilities and a fi sh market), training, mentoring, and fi eld visits. The programme has provided a range of benefi ts and positive impact including increasing in knowledge,production volume, and revenue KPI Mina Kepis members. Total member’s income before programme was Rp762.275.646 (2010), raised to Rp1.981.690.942 after CSR programme (2014). Good cooperation between the target group (recipient) and CSR programme partners (Bank Indonesia Yogyakarta, Sleman government, and the Department of Fisheries, Faculty of Agriculture UGM) has become one of the success factors for better performance indicators of the CSR programme at the target location.The objective of this research is to determine the type, benefi ts, and impact of Corporate SocialResponsibility (CSR) programs of Bank Indonesia on income of fi sh farmer group (KPI) Mina Kepis atSumberadi village, Sleman Regency. The study was conducted from January to March 2015. All member ofKPI were selected as respondents, with total number of 28 persons. The study showed that CSR programin the form of physical infrastructure assistance such as major production facilities (pool and hatchery)and supporting infrastructure (parking facilities and a fi sh market), training, mentoring, and fi eld visits.The programme has provided a range of benefi ts and positive impact including increasing in knowledge,production volume, and revenue KPI Mina Kepis members. Total member’s income before programmewas Rp762.275.646 (2010), raised to Rp1.981.690.942 after CSR programme (2014). Good cooperationbetween the target group (recipient) and CSR programme partners (Bank Indonesia Yogyakarta, Slemangovernment, and the Department of Fisheries, Faculty of Agriculture UGM) has become one of the successfactors for better performance indicators of the CSR programme at the target location.